Determination of selenium species and analysis of methyl-seleno-l-cysteine in Se-enriched mung bean sprouts by HPLC-MS. Issue 15 (31st March 2016) - Tie, Mei; Gao, Yu; Xue, Youlin; Zhang, Anning; Yao, Yi; Sun, Jifeng; Xue, Shuang
Abstract : Different species of selenium (Se) were determined in this study. Abstract : Different species of selenium (Se) were determined in this study. Graphite furnace atomic absorption spectrometry (GFAAS) was used to analyze the total Se content, soluble Se content and protein Se content. Se-methyl-seleno-l -cysteine (Se-MeSeCys) in Se-enriched mung bean sprouts was qualitatively and quantitatively analyzed by high performance liquid chromatography coupled with mass spectrometry (HPLC-MS). The results showed that added Se can significantly improve the total Se content in mung bean sprouts, reaching a concentration of 7275.0 μg kg −1 at the maximum concentration of Se. Acid-soluble Se was the major form of soluble Se in the mung bean sprouts. The content of protein Se in mung bean sprouts and added Se concentration were positively correlated, and the content of Se in protein accounted for 23.5% of the total Se when the added Se concentration was 12 mg L −1 . HPLC-MS results showed that the Se-MeSeCys content of Se-enriched mung bean sprouts in protease solution increased with increasing concentration of added Se, and the maximum was 615.5 μg kg −1 . The Se content in Se-MeSeCys accounted for 3.9% of the total Se concentration, which indicated that inorganic Se compounds can be transformed into organic Se compounds through biotransformation by mung bean sprouts.